CD28 costimulation: a source of Vav-1 for TCR signaling with the help of SLP-76? - Michel, F; Acuto, O (2002)
T cells require dual stimulation to become activated. When T cells encounter antigen-presenting cells, both the T cell receptor (TCR) and the CD28 coreceptor are ligated and activated. Michel and Acuto discuss how the adaptor SLP-76, which is recruited to the activated TCR complex, and the Rho family guanosine triphosphatase exchanger Vav-1, which is recruited by the CD28 receptor and TCR, may form a macromolecular complex that results in T cells activation. Vav-1 may serve as a central integrator between CD28 signaling and TCR signaling through its indirect effects on phosphoinositide 3-kinase-dependent signaling.